Assessment of Oxidative Status in Foot Diseases of Sheep - Yurdakul, Ibrahim; Yildirim, Betul Apaydin (Acta Scientiae Veterinariae, 2018)
Background: Oxidative stress plays an important role in the etiology and/or progression of various diseases in the livestock. The aim of this study was to investigate the relationship between foot diseases and oxidant and antioxidant levels, determining catalase (CAT) and glutathione peroxidase (GSH-Px) activities and malondialdehyde (MDA), nitric oxide (NO) and glutathione (GSH) concentrations in sheep with foot disease such as interdigital dermatitis, footrot and interdigital pouch infection (biflex canal inflammation). Materials, Methods & Results: In the study, a total of 70 sheep aged between 1 and 3, 20 sheep with interdigital dermatitis, 20 with foot-rot, 10 with interdigital pouch inflammation and 20 clinically healthy Akkaraman sheep, were used. The blood samples collected from the V. Jugularis of the sheep were centrifuged and their serums were obtained. MDA and NO levels of the sheep with interdigital dermatitis, footrot and interdigital pouch infection were found to be significantly higher than those of animals in the control group (P < 0.001). CAT activity was determined to be significantly lower in all diseased animals than in the animals in the control group (P < 0.001). GSH-Px and GSH levels were significantly lower in the animals with interdigital dermatitis than in the control group (respectively P < 0.001, P < 0.05). Discussion: Oxidative stress regulates the metabolic activity of some organs and plays an important role in productivity in livestock. The oxidative stress is reported that caused by the increase in the production of excessive free radicals resulting from the exposure of animals to various stress factors and by the weakening of the antioxidant defense has an important role in the pathogenesis of numerous diseases such as foot diseases. In the presence of various stress factors, the level of malondialdehyde (MDA) and nitric oxide (NO) increases. MDA is determine the degree of cellular damage in tissues. Nitric oxide is produced in large quantities by macrophages in case of bacterial infections and exhibits antibacterial properties against pathogenic microorganisms. For this reason, NO is very high levels in inflammatory diseases. Catalase (CAT), glutathione peroxidase (GSH-Px), and glutathione (GSH) is some of the important antioxidants and play an important role in the oxidative defense of tissues. In this study, the increase in serum MDA and NO levels was mostly found in interdigital dermatitis cases, then in footrot cases and finally in interdigital pouch infection cases. Serum CAT levels were found to be significantly lower than that of the control group (P < 0.001). In this study, the highest decrease in serum CAT levels was detected in interdigital dermatitis cases and followed by footrot cases and interdigital pouch infection cases, respectively. Serum GSH-Px and GSH levels were found to be significantly lower in interdigital dermatitis cases than those in the control group (respectively P < 0.001, P < 0.05). There was no statistically significant difference found between the serum GSH-Px and GSH levels of footrot and interdigital pouch infection cases, and the control group (P > 0.05). We found that serum MDA and NO levels were found to significantly increase in sheep with foot disease and serum CAT levels were found to be significantly lower. The results of this research indicate that MDA, NO and CAT activities may be more reliable parameters than GSH-Px and GSH activities in order to determine oxidative stress in sheep with foot diseases. In conclusion, this study reveals that there is a relationship between foot diseases and oxidant/antioxidant balance in sheep and it shows that the oxidative stress and lipid peroxidation develop due to the increase of free radicals.